The Managerial Ability Of Madrasa Principals, Work Climate And Work Motivation On Teacher Performance Madrasa Ibtidaiyah - Fajri, Pili; Sada, Heru Juabdin (Journal of Advanced Islamic Educational Management, 2024)
This study aims to determine the effect of the variables of managerial ability of the madrasa head, work climate and work motivation on the performance of teachers of the State Madrasa Ibtidaiyah in Bandar Lampung. Madrasas that are the object of this research are MIN 1, MIN 5 and MIN 6 in Bandar Lampung. The data used in this study used primary data obtained from questionnaire data distributed to teachers working in MIN 1, MIN 5 and MIN 6 Bandar Lampung who have civil servant status for more than 3 years. The sample used was 50 respondents. The sample withdrawal used by the author is Non Probability Sampling with Purposive Sampling method. The results of the study simultaneously showed that all the independent variables, namely the managerial ability of the madrasa head, work climate and work motivation together had an effect on the performance of teachers of the State Madrasa Ibtidaiyah in Bandar Lampung.